Evaluasi Kebijakan Penanganan Covid-19 Pemerintah Provinsi Jawa Barat : (Evaluation of the West Java Provincial Government's Policy on Covid-19) - Lia Fitrianingrum (JPSI (Journal of Public Sector Innovations), 2021)
This study evaluates the West Java Provincial Government's policy in handling the Covid-19 pandemic by focusing on organizational, substance, and political aspects by mapping targets, supporting factors, obstacles, and impact analysis. The Covid-19 pandemic has brought a tremendous impact on the health sector and economic growth in West Java. Policies related to the pandemic handling by West Java Provincial Government in synergy with the Central Government and Regency/City Governments have been carried out intensely and continuously since the beginning of 2020. Various stimuli were carried out by the West Java government to reduce the spread of Covid-19 as well as to recover economic condition in West Java. The wave of Covid-19 has occurred twice, at the end of 2020 and after Eid in 2021. Various policies have been implemented, and after almost one and half years of running, that policy can be evaluated. This research used the qualitative method. Data collection techniques were carried out by collecting secondary data, observation and interviews. The study results showed that the Covid-19 handling policy in West Java Province, apart from organizational, substance and political elements, a crucial element as the driving force for the optimal COVID-19 handling policy was the community support and participation (human society), which had been tested during the crisis. It is proven that currently, West Java Provincial Government can reduce the mortality rate of COVID-19 patients and the occupancy of hospital beds below WHO standards. The limitations of this research only look at the three elements that become the instrument of policy evaluation. The policy recommendations offered are implementing a stimulus program in the form of affirmative policies and program-based budget support in the work to reactivate the real sector and encourage the growth of people's purchasing power and create a communication forum that can promote economic recovery in West Java.   Abstrak Artikel ini membahas evaluasi kebijakan penanganan Covid-19 Pemerintah Provinsi Jawa Barat dengan menitikberatkan kepada aspek organisasi, aspek substansi dan aspek politis dalam penanganan Covid-19 dengan melakukan pemetaan sasaran, faktor pendukung, penghambat dan analisis dampaknya. Pandemi Covid-19 telah membawa dampak yang luarbiasa di sektor kesehatan dan pertumbuhan ekonomi di Jawa Barat. Kebijakan yang dilakukan Pemerintah Provinsi Jawa barat bersinergi dengan Pemerintah Pusat dan Kabupaten/Kota dilakukan secara intens dan berkelanjutan sejak awal tahun 2020. Berbagai stimulus dilakukan oleh Pemerintah Jawa Barat guna menurunkan angka penyebaran Covid-19 dan pemulihan ekonomi. Gelombang lonjakan Covid-19 sudah terjadi dua kali yaitu di akhir tahun 2020 dan pasca lebaran tahun 2021. Berbagai kebijakan telah diimplementasikan, dan setelah hampir satu setengah tahun berjalan, kebijakan penanganan Covid-19 ini sudah dapat dievaluasi. Metode yang digunakan dalam penelitian ini adalah metode kualitatif dengan teknik pengumpulan data dilakukan dengan data sekunder, observasi dan wawancara. Hasil kajian menunjukkan bahwa evaluasi kebijakan penanganan Covid-19 di Provinsi Jawa barat selain melibatkan unsur organisasi, substansi dan politis maka ada unsur yang sangat penting yang merupakan pendorong kebijakan penanganan covid ini optimal, yaitu dukungan dan partisipasi masyarakat (human society). Pentingnya peran mereka telah teruji di masa krisis dan terbukti bahwa saat ini Pemerintah Provinsi Jawa barat dapat menurunkan angka kematian pasien Covid-19 dan keterisian tempat tidur rumah sakit di bawah standar WHO. Rekomendasi kebijakan yang ditawarkan adalah dijalankannya program stimulus berupa kebijakan afirmatif serta dukungan anggaran berbasis program pada karya untuk menggerakan kembali sektor riil serta mendorong pertumbuhan daya beli masyarakat, dan di buatnya forum komunikasi yang dapat mendorong pemulihan ekonomi di Jawa Barat. Keterbatasan penelitian ini adalah kajian hanya melihat dari ketiga unsur yang menjadi instrument evaluasi kebijakan. Kata kunci: evaluasi kebijakan, Covid-19, Pemerintah Provinsi Jawa Barat